The Influence of Motivation and Organizational Culture on Employee Competence at Agency X - Lesmini, Indah; Nurani, Nina (Dinasti Publisher, 2025)
This study seeks to investigate the effect of motivation and organizational culture on employee competence within Agency X. Employee competence plays a vital role in improving work efficiency and the quality of public service delivery. A quantitative research design with a survey method was employed. Data were obtained through questionnaires distributed to 143 active employees of Agency X. The data were analyzed using multiple linear regression with the assistance of SPSS version 26.0. The results indicate that both motivation and organizational culture have a significant influence on employee competence. Specifically, motivation positively affects competence, meaning that higher levels of employee motivation correspond to greater competence. Furthermore, organizational culture also exerts a significant impact, suggesting that a supportive work environment grounded in strong organizational values can enhance employee performance and overall work quality.